Research libraries and the internet: On the transformative dynamic between institutions and digital media. Issue 2 (2014) - ,
Abstract : Purpose – The purpose of this paper is to improve comprehension of some of the intricate interrelations between research libraries, the role of media and the knowledge production system.Design/methodology/approach – This paper establishes arguments from a historical analysis of stages in the conceptual development of digital media and stages in the digitization of library functions. The historical approach leads to some discussions and forecasts of the future of research libraries.Findings – Digital media have a disruptive, revolutionary potential, but path dependency is often a modifying component in the historical development. This is demonstrated in different stages of the development of the interrelationship between digitization, digital media and research libraries. Digital media become disruptive due to the strength of the historical dynamic, rather than as a result of particular agencies. Today the historical dynamic has reached a point where all institutions concerned with knowledge handling will have to redefine themselves. Research libraries are gradually incorporated into a number of new "research infrastructures" which are being built around different kinds of data materials, and each research library may specialize according to some sort of coordinated criteria.Originality/value – This paper demonstrates new openings to a theoretical and conceptual understanding of the interrelationship between digital media and developments of research libraries.